British Columbia & the Canadian Rockies - Lee, John; Sainsbury, Brendan; Ver Berkmoes, Ryan; Lonely Planet Publications (Firm) (Oakland, CA Lonely Planet, 2014)
Lonely Planet British Columbia and the Canadian Rockies is your passport to all the most relevant and up-to-date advice on what to see, what to skip, and what hidden discoveries await you. Watch wildlife in Jasper National Park, stroll the seawall at Vancouver's Stanley Park, and set sail on a ferry service through the Inside Passage; all with your trusted travel companion. Get to the heart of British Columbia and the Canadian Rockies and begin your journey now!
"Vancouver pull-out map"--Cover.
Previous ed.: 2011.
Includes index.
Keywords: Travel; British Columbia; Canadian Rockies (B.C. and Alta.); British Columbia -- Description and travel; Canadian Rockies (B.C. and Alta.) -- Description and travel; Canada -- Canadian Rockies; Guidebooks